Validitas konstruk dan reliabilitas tes-ulang dari tes kelancaran kata emosi bahasa Indonesia yang dilaksanakan secara daring dengan supervisi - Heni Gerda Pesau; Gilles van Luijtelaar (Jurnal Psikologi Ulayat, 2026)
The emotion word fluency test (EWFT), measuring the ability to produce emotional words, may measure a different cognitive construct of verbal flexibility than the commonly used phonemic (PVFT) and semantic (SVFT) verbal fluency tests. This was hypothesized and tested through Principal Component Analyses (PCA) of the test scores of 150 healthy subjects. The test-retest reliability was additionally examined after two weeks in forty subjects. Data was collected through supervised internet-delivered testing. Correlation analyses for construct validity showed that the EWFT correlated only moderately with PVFT and SVFT. PCA showed that a three-factor model explained 68.5% of the total variance. The subscales of each fluency test loaded primarily on separate factors, indicating that the three tests measure different underlying constructs. The test-retest revealed moderate reliability without a clear repetition/practice effect. It can be concluded that the supervised Indonesian online-administered EWFT measures emotion processing abilities. However, it awaits clinical validation in various clinical populations.